Enhancing Innovativeness in Startups through Quality Management Practices: A Managerial Perspective - Andreas Mahendro Kuncoro (Journal of Trends Economics and Accounting Research, 2023)
Startups characterized by focusing on innovativeness require suitable management approach in order to sustain in dynamic, complex and uncertain environment. Quality management practice has been world-widely implemented in any organizations, but limited studies have been conducted to examine the relationship between quality management and innovativeness in startups. A systematic literature review was conducted and resulted in 29 selected papers. This paper aims to bridge the gap by providing managerial insights on how startups can enhance their innovativeness through quality management practices. The study concluded that understanding the interrelationships between the principles of quality management practices provides support to quality culture, continuous organization learning to create value as sources to enhance innovation